Mitochondrial calcium handling in normotensive and spontaneously hypertensive rats: Correlation with systolic blood pressure levels - Ciocci Pardo, Alejandro (2015)
The aim was to study the mitochondrial Ca2+ handling of mitochondria isolated from normotensive Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHR) hearts and to establish a possible correlation with systolic blood pressure (SBP). Mitochondrial swelling after Ca2+ addition, Ca2+-retention capacity (CRC) by calcium green method, and membrane potential (ΔΨm) were assessed. SBP was 124 ± 1 (WKY) and 235 ± 6 mm Hg (SHR). CRC, Ca2+ response and ΔΨm were lower in SHR than WKY mitochondria. The conclusion is: the more depolarized state of SHR than WKY mitochondria results in an abnormal Ca2+ handling and this event is closely associated with the SBP.